Collaborative Colonialism - Askari, H. author. aut Link
XIX, 198 p. 3 illus.
Keywords: This book is an analysis of how oil has affected governance and human, political, and economic development in the countries of the Persian Gulf and shaped these countries' relations with the rest of the world.